Levy solution for bending analysis of functionally graded sandwich plates based on four variable plate theory. (1st October 2017) - Demirhan, Pinar Aydan; Taskin, Vedat
Abstract: In the present study, static analysis of a functionally graded sandwich plate with two opposite simply supported edges is studied using a four variable refined plate theory. The core of sandwich plate is assumed isotropic and material properties of face layers are assumed graded through thickness direction by the power law. Displacement fields are defined by using the four variable plate theory. Equilibrium equations of the sandwich plate are obtained using virtual work principle. Levy type solution with state space concept is used to derive governing equations. The results of deflection, normal and shear stress of uniformly loaded functionally graded square sandwich plates with two opposite simply supported edges are presented. The accuracy of the solution is verified by comparing it with available results in the literature.